2020
DOI: 10.7759/cureus.7681
|View full text |Cite
|
Sign up to set email alerts
|

Batter’s Shoulder: Clinical Outcomes and Return to Sport

Abstract: Background Batter's shoulder has been defined as an acute posterior subluxation of the lead shoulder during a baseball swing causing a traumatic tear of the posterior labrum. There are limited data correlating repair techniques with return-to-play information but none utilizing standardized outcome measures. The purpose of this study is to examine a case series of patients for postoperative return-to-play and obtain follow-up using standardized outcome measures. Methods We retrospectively identified 10 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Recent studies have shown, regardless of fixation technique, between 91% and 100% of athletes with a Batter’s Shoulder injury are able to return to their previous level of play following arthroscopic treatment with posterior labral fixation. 9 , 10 While these studies illustrate the benefits of arthroscopic fixation of a Batter’s Shoulder injury, they fail to identify the specifics of the techniques and fixation used. This technical note provides a reproducible method of arthroscopic fixation for this specific injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown, regardless of fixation technique, between 91% and 100% of athletes with a Batter’s Shoulder injury are able to return to their previous level of play following arthroscopic treatment with posterior labral fixation. 9 , 10 While these studies illustrate the benefits of arthroscopic fixation of a Batter’s Shoulder injury, they fail to identify the specifics of the techniques and fixation used. This technical note provides a reproducible method of arthroscopic fixation for this specific injury.…”
Section: Discussionmentioning
confidence: 99%
“…Knotted fixation has been the traditional method of fixation in arthroscopic labral repair. 10 There has been a shift toward knotless fixation for anterior labral tears due to less knot abrasion, but there is a lack of research looking at knotless repairs of Batter’s Shoulder. Research looking at biomechanics and clinical outcomes on anterior labral tears, could suggest there is a benefit in using knotless fixation for a Batter’s Shoulder injury.…”
Section: Discussionmentioning
confidence: 99%
“…Batting may also contribute to injury. 24,25 Although less frequent than pitchers, position players still place considerable force on their arms. Position players also generally do not have a "pitch count" to track the number of throws to help prevent injury.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, hitting can lead to posterior instability or batter's shoulder, which occurs as the adducted lead arm absorbs a posteriorly directed force during the swinging motion, resulting in posterior subluxation/dislocation with spontaneous reduction. 29 Diagnosis is difficult because patients often present with pain rather than gross instability (75% vs 3%). 28 On occasion players may be able to recount a specific, traumatic event that caused the symptoms, but many times this is non-specific.…”
Section: Posterior Shoulder Instabilitymentioning
confidence: 99%